Islamic Views and Calls to Invest According to the Al-Qur'an Surah Al-Hashr Verse 18 - Istianah Liizzah; Achmad Agus Priyono; Dewi Masitah (Dirasah International Journal of Islamic Studies, 2023)
Investing in Islam is a highly recommended activity. This is explicitly stated in various verses such as QS. Al-Hashr: 18, QS. Lukman: 34, and others. Not all types of investment are allowed in Islam. Only investments that are in accordance with Islamic teachings may be followed by Muslim investors. These principles include the types of businesses and transactions that must follow Islamic Sharia norms. This means that, in the type of business, products or services provided and the way the company is managed, the issuer company is not a business that is prohibited by sharia, such as gambling business, prohibited trade, not ribawi finance or conventional banking and insurance, not producers, distributors, and food and beverage traders. which is forbidden. not a business/company either producer or distributor that provides goods or services that can damage morals and are harmful. Likewise, the type of transaction must be carried out with the principle of being very careful, it is not permissible to speculate in which there are elements of gharar, maysir, dzulm, tadlis, and so on. The rise of fraudulent investment cases under the guise of investing makes us aware of what investment in Islam really is.